Cervical polyp: histomorphological spectrum of ninety-two cases a five-year study - Kundu, Parveen Rana; Hooda, Sunaina; ., Parul; Singh, Kulwant; Agarwal, Ruchi; Kaur, Swaran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervix is vulnerable to many pathological changes ranging from inflammation to malignancy. Cervical polyp is one of the commonest cervical lesion seen in about 2-5% of women. They are more frequent in parous women and are mostly asymptomatic. Symptomatic polyps are frequent in the premenopausal women with most common clinical presentation of AUB(abnormal uterine bleed). Usually they are benign but there are chances of malignant transformation. This study was done to analyse the clinico-pathological spectrum of cervical polyp at a tertiary care institute Methods: A retrospective study was conducted in department of Pathology, BPS GMC for Women Khanpur Kalan, Sonepat over a period of 5 years. All patients who had been diagnosed with cervical polyp clinically and underwent subsequent histopathological sampling were included. Results: A total of 92 cases were included in the study. AUB was the most common clinical presentation of these patients with cervical polyp. Most common age group was 30 to 55 years. Out of 92 cases 47 were of endocervical type polyp, followed by 20 cases of leiomyomatous polyp Conclusions: To conclude in this study we found that the most common type of cervical polyp is endocervical type. Keeping in view the malignant transformation histopathological sampling of polyp is essential.